Prepositions In Arabic And English: A Comparative And Contrastive Analysis - Djeribiai, Adel (جامعة الوادي - University of Eloued, 2022)
This study attempts a comparative and contrastive analysis of the subsystems of the prepositions in Arabic and English, in terms of their uses, function and meanings in order to find the major similarities and differences between Arabic and English and to account for any possible deviations that may characterize the performance of Arabic learners. The result showed that there are similarities and differences between these two subsystems of the prepositions in Arabic and English. The similarities between them facilitate the development process of learning a foreign language (positive transfer), whereas differences make learning process of a foreign language difficult and Arabic learners make many mistakes (negative transfer or interference).This study has pedagogical implications for teaching prepositions in English and to help teachers and motivate them to describe and analyze the learners' errors and also to prepare remedial exercises to eliminate the errors their students make in the use of prepositions
articl
Keywords: Prepositions ; English ; MSA ; idiosyncrasies